Implikasi Hukum Perkawinan Bagi Umat Beragama Nasrani yang Perkawinannya Tidak Dicatatkan di Kantor Catatan Sipil (Studi Penelitian di Gereja Bethel Indonesia Jemaat Gosyen Lubuk Pakam) - Sirait, Elisabet; Bintang, Hasdiana Juwita; Siagian, Asman (Jurnal Christian Humaniora, 2025)
Marriage that is not officially registered with the Civil Registry Office remains a serious legal issue, particularly among Christian communities in Indonesia. Although such marriages are considered religiously valid through church blessings, their lack of state registration gives rise to various legal implications, especially concerning the legal status of children, inheritance rights, and legal protection for the spouses. This study aims to conduct an in-depth analysis. In this regard, the discussion focuses on the legal impacts on the status of children, limitations on inheritance rights, obstacles in obtaining administrative documents, and uncertainty in determining the status of marital property, with a particular focus on the case study of the congregation of the Bethel Church of Indonesia, Gosyen Lubuk Pakam. The research employs a qualitative method with a case study approach, combining primary data collected through interviews with church leaders and couples whose marriages are unregistered, as well as direct observations of church activities. Secondary data is drawn from legal literature and regulations, such as Law No. 1 of 1974 in conjunction with Law No. 16 of 2019 on Marriage, Constitutional Court Decision No. 46/PUU-VIII/2010, and Supreme Court jurisprudence related to the legal status of children and inheritance rights. The findings indicate that unregistered marriages have broad impacts on the legal standing of children, restrictions on inheritance rights, and limited access to administrative services such as birth certificates and social security. Furthermore, the absence of registration also creates uncertainty in determining the status of marital property.